Complications of anticoagulant therapy after surgical interventions on the vertebral column - Petrenko, Dmytro; Voloshin, Mykyta; Mezentsev, Andrey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article contains results of a literature review and the authors’ own experience in aspects of postoperative anticoagulation therapy in patients, who survived surgical interventions on their vertebral column. As a result of the research, it was revealed that venous filters were the most effective means for preventing thromboembolic complications. The use of anticoagulant agents was accompanied by an acceptable rate of complications, heparin being the most optimum drug. But at present it is necessary to develop a protocol for anticoagulation therapy in patients after operations on the vertebral column.